C‐Shaped Cartilage Development Using Wharton's Jelly‐Derived Hydrogels to Assemble a Highly Biomimetic Neotrachea for use in Circumferential Tracheal Reconstruction. (17th January 2023) - Gao, Erji; Wang, Yao; Wang, Pengli; Wang, Qianyi; Wei, Yuxuan; Song, Daiying; Xu, Huangfang; Ding, Jinghao; Xu, Yong; Xia, Huitang; Chen, Ru; Duan, Liang
Abstract: A highly biomimetic neotrachea with C‐shaped cartilage rings has promising clinical applications in the treatment of circumferential tracheal defects (CTDs) owing to its structure and physiological function. However, to date, most fabricated tracheal cartilages are O‐shaped. In this study, finite element analysis demonstrates C‐shaped cartilage rings that exhibit better compliance than O‐shaped. Hydrogel is developed using methacryloyl‐modified decellularized Wharton's jelly matrix (DWJMA) for the regeneration of C‐shaped cartilage rings. This novel hydrogel possesses adjustable physicochemical properties and favorable cytocompatibility. When loaded with chondrocytes, DWJMA hydrogels support the optimal cartilage regeneration both in vitro and in vivo. More importantly, a highly biomimetic neotrachea simultaneously simulating the structural and physiological properties of the normal trachea is regenerated via modular assembly of several individual C‐shaped cartilage rings. The results demonstrate the highly biomimetic neotrachea have better patency (88.6 ± 6.1% vs 74.4 ± 9.4%, p  < 0.05), improve the survival rate, alleviate weight loss and mucoid impaction, than its O‐shaped counterpart when used for the treatment of CTDs in a rabbit model. Therefore, this study proposes a novel hydrogel for the regeneration of C‐shaped cartilage and provides new insights into the treatment of CTDs using a highly biomimetic neotrachea with C‐shaped cartilage rings. Abstract : A novel native‐tissue derived hydrogel is fabricated using decellularized Wharton's jelly to regenerate C‐shaped cartilage. Then, a highly biomimetic neotrachea with several individual C‐shaped cartilage rings, which simultaneously simulates the structural and physiological properties of the normal trachea is assembled and applied in a rabbit model of circumferential tracheal defect.